Crystal Structure, Phase Transitions and Photoferroelectric Properties of KNbO3-Based Lead-Free Ferroelectric Ceramics: A Brief Review - Wang, Dawei; Wang, Ge; Lu, Zhilun; Al-Jlaihawi, Zaid; Feteira, Antonio (Frontiers in Materials, 2020)
Ferroelectric KNbO3 (KN) ceramics were first fabricated in the 1950s, however their use in commercial technical applications has been hampered by inherently challenging processing difficulties. In the early 1990s, the interest in KN ceramics was revived by the pursuit of Pb-free piezoceramics. More recently the search for inexpensive photovoltaic materials alternative to Si prompted bandgap engineering studies in KN-based solid solutions. If the ferroelectric and piezoelectric properties of KN-based ceramics are now well established, the understanding of chemical doping on the bandgap of KN-based ceramics is still in its infancy. Here we provide a brief review on the current understanding of the structure-property relationships in this class of materials, which successively covers crystal structures, structural phase transitions, lattice dynamics, polarization, solid solutions and bandgap engineering of KN.